2015
DOI: 10.18410/jebmh/2015/114
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Thyroid Lesions in Wardha District of Central India

Abstract: To establish a significant predominance of thyroid lesions in and around Wardha district, and to establish specific etiological link for the predominance the thyroid lesions. MATERIALS AND METHODS: This was a hospital based analytical prospective study, conducted in Acharya Vinobha Bhave Rural Hospital (A.V.B.R.H.) involving 108 patients. The study was carried over a duration of 1 year January 2010 to December 2010. Patients attending endocrinological clinics and the newly detected cases of thyroid lesions, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The prevalence of these thyroid disorders varies widely according to geographical distribution, diet and nutrition, and patient population [ 1 , 2 ]. Thyroiditis a diverse group of disorder characterized by thyroid inflammation and have different etiologies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of these thyroid disorders varies widely according to geographical distribution, diet and nutrition, and patient population [ 1 , 2 ]. Thyroiditis a diverse group of disorder characterized by thyroid inflammation and have different etiologies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a study done in Colombia (2018) the prevalence of thyroid stimulating hormone (TSH) was 24.5%, 19% of people had a high prevalence of this hormone, being higher in women (Carmona Carmona et al, 2018). Moreover, Indian study for the prevalence of thyroid disorders in 2015 reported that, almost one-third of the world's population lives in areas of iodine deficiency and account for an estimated 200 million cases worldwide and 42 million cases in India itself (Shukla et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of thyroid disorders varies widely according to geographical distribution, diet, nutrition, and patient population. 2,3 Thyroiditis is a diverse group of disorder characterized by thyroid inflammation and have different aetiologies. 4 It can be categorized as acute, subacute or chronic forms.…”
mentioning
confidence: 99%